Short-Term Complications following Single-Session versus Staged Bilateral Tibial Plateau Levelling Osteotomies Stabilized with Locking Plates for Treatment of Bilateral Cranial Cruciate Ligament Disease: A Retrospective Study - Cappelle, Kelsey K.; Barnhart, Matthew D. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to compare complications between dogs with bilateral cranial cruciate ligament disease treated with single-session bilateral tibial plateau levelling osteotomies (BSSTPLO) versus staged bilateral TPLO (STPLO) procedures stabilized with locking plates.Study Design Medical records of client-owned dogs treated with BSSTPLO or STPLO stabilized with locking plates between March 2017 and July 2018 at two associated institutions were reviewed. Patient data and complications from 37 dogs with BSSTPLO and 18 with STPLO were compared between groups. Major complications were defined as any complication that required further surgical or medical treatment whereas minor complications did not.Results Incidence for major complications for BSSTPLO and STPLO was 7/37 and 6/18 respectively. Incidence for minor complications for BSSTPLO and STPLO was 3/37 and 2/18 respectively. No significant differences in minor or major complication rates existed between study groups (p = 0.2). Mean body weight was significantly higher in the STPLO group (p = 0.001); however, no correlation between weight or BCS and complication rate existed within either group. Increasing age was the only significant risk factor for major complications (p = 0.01) in either group.Conclusion Our findings support the claim that BSSTPLO and STPLO performed with locking implants have similar complication rates. The decision to perform BSSTPLO or STPLO in dogs with bilateral cranial cruciate ligament disease should be based on other considerations rather than just complication rates.
Keywords: cranial cruciate ligament rupture; bilateral; complications; locking plates; tibial plateau levelling osteotomy